The Analysis of Cohesive Devices Found in Good-Bye - Sandra Putri Astariani, Putu (Udayana Journal of Social Sciences and Humanities; Vol 4 No 1 (2020): UJoSSH, February 2020DO - 10.24843/UJoSSH.2020.v04.i01.p08, 2020)
The basic definition of discourse is a language above sentences which is a cohesive, coherent, and functional. Cohesion and coherence are two vital elements constituting a discourse which are supported by the cohesive devices, i.e. reference, substitution, ellipsis, conjunctions, and lexical cohesion. This article discusses the cohesion and coherence of discourse through the identification of its cohesive devices. An anecdote entitled Good-Bye is selected due to its simplicity yet intriguing language, therefore the subliminal messages can be delivered and revealed. By using the qualitative approach and method, the results of the analysis, covering the cohesive devices within the text, can be comprehensively described. The analysis was carried based on the theory of functional grammar by MAK Halliday from his book Halliday's Introduction to Functional Grammar by MAK Halliday (revised by Christian MIM Matthiessen), about the cohesive devices. In addition to this one, the theory of cohesive devices from the book Cohesion in English by MAK Halliday and Ruqaiyah Hasan is used as a supporting theory. Within this anecdote, four out of five cohesive devices proposed by Halliday and Hasan were found. They covered the reference, ellipsis, conjunction, and lexical cohesion (reiteration and collocation). Unfortunately, substitution could not be found.